Establishment of Islamic Law based on Mukhtalif Hadiths: A Study on Ibn Qutaybah's Thoughts - Muthalib, Salman Abdul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Islamic law should be based on clear and proven evidence, both in the Qur’an and in the authentic hadiths, while the existence of mukhtalif hadiths can cause confusion in making decisions and determining the legal certainty that governs the issue. This study will elaborate on the methods used by scholars in determining the law based on conflicting hadiths. The research results indicate that there are three steps that scholars take in producing laws derived from mukhtalif hadiths: the methods of al-Jam’u wa al-Taufiq, al-Nash, and tarjih. In the method of al-Jam’ wa al-tawfiq, there is a linguistic approach, interpretation, and reduction of meaning, as well as the conditions under which a hadith was uttered and the reinterpretation of the wording of the hadith to a different meaning. In the method of al-nasikh wa al-mansukh, Ibn Qutaybah did not provide a detailed explanation of when, where, and in what case the hadith was uttered. In the method of tarjih, the focus is on the quality of the sanad, where the proximity of the relationship between the narrator and the Prophet is the main consideration for strengthening one hadith.